RELEVANSI AJARAN ADVAITA VEDANTA DALAM MENANGKAL UJARAN KEBENCIAN DAN HOAX - I Dewa Gede Agus Priana Putra; Yunitha Asri Diantary Ni Made (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2021)
The development of technology that is increasingly making human life easier in various aspects has a positive and negative impact. Various facilities offered by modern technology provide space for humans to be creative in their use, but on the other hand humans use their creativity space by spreading false information as a form of self-existence and criticizing or bringing down opponents. The spread of false information or known as hoaxes is deliberately made to influence the public and is increasingly widespread due to stimulant factors such as socio-political issues and SARA. but hoax recipients are quite critical because they are used to checking the truth of the news, so it is important that in dealing with hoax information, people need to apply religious teachings, one of which is Vedanta teachings which will provide an understanding of true life, where humans live from the holy and also side by side with good and bad, so it is important for mankind to exercise self-control by carrying out the jnana marga path as a way to achieve the goal of warding off hate speech and hoaxes.Keywords: relevance of vedanta teachings, counteracting hate speech, hoaxes